RELIGIOUS BLASPHEMY AND MONITORY SOCIETY IN INDONESIAN DIGITAL AGE - Leonard Chrysostomos Epafras; Hendrikus Paulus Kaunang; Syamsul Asri (Universitas Gadjah Mada, 2019)
The present article is a research report on the discourse of religious blasphemy in connection with digital practices in Indonesia. It sought to understand the shift of public participation in shaping the discourse that understood within the framework we identified as “monitory society.” The research employed qualitative approach by using several methods, among others are interview and social media observation. Reflecting upon the current national trends and new shift of political landscape, it appeared that religious blasphemy immersed into the political discourse as weaponized information, hence disrupted the meaning of democracy in digital age, as once become the rhetoric of digital technology. In general, the discourse of religious blasphemy in Indonesia is dealing with public piety and social order. It concerned more on religious boundary rather than the improvement of religious lives and personal piety.